Comparative morphological and anatomical features of the leaves of the species Paulownia Siebold & Zucc - Калдыбаева, Ж.Б.; Курманбаева, М.С. (Fundamental and Experimental Biology, 2023)
The article describes for the first time the features of the morphological and anatomical structure of the leaves of the hybrids Shan Tong and FTE of the species Paulownia Siebold & Zucc, grown in the conditions of Almaty. This type of tree is widely distributed in natural conditions in the countries of Southeast Asia. It is currently cultivated in many countries. Relevance of the work: Paulownia wood is widely used in the forestry industry, for the production of biofuels and biogas, as a bioremediant and in medicine. It is cultivated in Kazakhstan for the first time, and therefore biological and ecological studies of Paulownia hybrids have not been carried out in local environmental conditions. Given its practical significance, it is extremely necessary for our country, which is experiencing a shortage of forest, to use the capabilities of this tree. Aims and objectives of the work: to study and compare the morphological and anatomical features of the leaves of the Shan Tong and FTE hybrids of the Paulownia species. Research methods: morphometric indicators and morphological structure of organs were carried out according to the generally accepted methodology. For microscopic analysis, fixation was performed by the Strasburger-Flemming method. Result: the concentration sites of biologically active substances were established when identifying diagnostic signs of the anatomical structure of the leaves of Shan Tong and FTE, and it was also found that glycosides are concentrated in columnar and loose mesophyll. Microscopic sections revealed that in the anatomical structure of the leaf there are simple multicellular mononuclear trichomes, unicellular glandular hairs, unbranched pitcher-shaped, multicellular, mononuclear large trichomes. The comparison revealed that the morphometric parameters of the FTE hybrid leaf are higher than the morphometric parameters of the Shan Tong hybrid leaf, the difference was observed only in the thickness of the columnar mesophyll. The obtained results make it possible to identify the anatomical features of the leaves of related Paulownia species, as well as to confirm, clarify and supplement the data. The data obtained can be used for systematic studies of related species of Paulownia in practical use.